2015
DOI: 10.4081/gh.2015.382
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan urban hotspots of chronic sleep deprivation: evidence from a community health survey in Gyeongbuk Province, South Korea

Abstract: The geographic concentration of chronic sleep deprivation (CSD) remains largely unexplored. This paper examined the community-specific spatial pattern of the prevalence of CSD and the presence of clustered spatial hotspots among the Korean elderly population in Gyeongbuk Province, South Korea, revealing CSD hotspots and underscoring the importance of geography-focused prevention strategies. The study analysed cross-sectional data collected from 9847 elderly individuals aged 60 years and older who participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Many health relevant environmental influences that are not directly measurable can only be described by a proxy of urban structure [60,67,139,165]. As these proxies can be assessed at different spatial scales from the level of an entire city to the level of single streets, they must be captured at various levels.…”
Section: (Intra-) Urban Structurementioning
confidence: 99%
“…Many health relevant environmental influences that are not directly measurable can only be described by a proxy of urban structure [60,67,139,165]. As these proxies can be assessed at different spatial scales from the level of an entire city to the level of single streets, they must be captured at various levels.…”
Section: (Intra-) Urban Structurementioning
confidence: 99%
“…Following a night of poor sleep, women appear to be at elevated risk of experiencing impairments throughout the day, e.g., (excessive) daytime tiredness, apathetic or irritable mood and reduced vigilance during daily activities, compared with men (Doi et al, 2001; Grandner, Martin, et al, 2012; Huang et al, 2010; Kronholm et al, 2015; Suh et al, 2020). Furthermore, studies have reported a higher prevalence of non‐restorative sleep and self‐perceived inadequate sleepers in women compared to men (Eaton et al, 2010; Grandner, Jackson, et al, 2015; Ohayon et al, 2000; Peltzer, 2017; Tang et al, 2017; Um & Um, 2015). Notably, adult women report the use of sleep medication more frequently compared to men (Fernandez‐Mendoza et al, 2012; Kocevska et al, 2021; Middelkoop et al, 1996).…”
Section: Sex and Sleepmentioning
confidence: 99%
“…Research shows similar patterns for schoolchildren and adolescents (Gradisar et al, 2011; Liu et al, 2005). Adults from East and Southeast Asia (Dong et al, 2018; Ryu et al, 2011; Tang et al, 2017; Thichumpa et al, 2018; Um & Um, 2015; Wang et al, 2020; Wu et al, 2018), Central and Southern America (Carrillo‐Larco et al, 2014; Lima et al, 2012; Neutzling et al, 2020; Soldatos et al, 2005), Sub‐Saharan Africa (Ade et al, 2021; Peltzer, 2017; Soldatos et al, 2005), The Middle East (Asghari et al, 2012; Chami et al, 2020), and urban regions in North America (Grandner, Smith, et al, 2015) are more likely to report sleep of poor quality (range 28%–50%, generally higher in rural areas) and short duration (range 12%–39%, generally higher in metropolitan urban areas) than adults residing in Europe, Japan, Australia and non‐urban regions in North America (Adams et al, 2017; Doi et al, 2001; Kocevska et al, 2021; Lakerveld et al, 2016; Liu et al, 2000). In most Western countries, the average self‐reported sleep duration (from ~7 h/night in Japan to 8.5 h/night in Portugal) and indicators of poor sleep quality (range 9%–30%, depending on the indicator assessed) are relatively comparable between populations (Adams et al, 2017; Doi et al, 2000; Groeger et al, 2004; Kocevska et al, 2021; Kronholm et al, 2006; Soldatos et al, 2005).…”
Section: Origin and Sleepmentioning
confidence: 99%
See 1 more Smart Citation